PENGETAHUAN DAN SIKAP REMAJA TERHADAP DISMENOREA DI SMP PNIEL MANADO - Tampake, Reny A.; Wagey, F.; Rarung, M (e-CliniC, 2014)
Abstract: Dismenorhea or painful menstruation, is one of the most common gynecological disorder. Dysmenorrhoea can be primary, if not accompanied by organic pathology, or secondary when accompanied by pathological disorders. Primary dysmenorrhoea is caused uterine contraction induced by prostaglandin and tends to occur with the onset of ovulatory cycles and usually improve over time, coinciding with the onset of menstrual bleeding. Primary dysmenorrhea peaks in the late teens and early 20s. Dismenorhea affect the lives of young people in various levels of daily activities. This study aims to examine the level of knowledge about the teenage daughter of dysmenorrhoea. This study is an analysis of cross-sectional descriptive study. Results of the study: the age distribution of respondents in the most junior Pniel Manado is 13-15 years (70.7 %), knowledge about adolescent dysmenorrhea is either approximately 77.6 %, positive student attitudes about Dismenorhea of 74.1 %. Keywords: dismenorrhea, adolescent, knowledge, attitude.Â Abstrak: Dismenorhea atau nyeri haid, adalah salah satu gangguan ginekologi yang paling umum. Dismenorea bisa primer, jika tidak disertai dengan patologi organik, atau sekunder jika disertai dengan gangguan patologis. Dismenorea primer disebabkan kontraksi uterus yang disebabkan oleh prostaglandin dan cenderung terjadi dengan timbulnya siklus ovulasi dan biasanya membaik dari waktu ke waktu, bertepatan dengan terjadinya perdarahan menstruasi. Puncak dismenore primer pada remaja akhir dan awal 20-an. Dismenorhea mempengaruhi kehidupan anak muda di berbagai tingkat aktivitas sehari-hari. Penelitian ini bertujuan untuk menguji tingkat pengetahuan tentang dismenorea putri remaja. Penelitian ini merupakan analisis dari penelitian deskriptif cross-sectional. Hasil penelitian: distribusi usia responden yang paling junior Pniel Manado adalah 13-15 tahun (70,7%), pengetahuan tentang dismenore remaja adalah baik sekitar 77,6%, sikap siswa positif tentang Dismenorhea dari 74,1%. Kata kunci: Dismenorea, remaja, pengetahuan, sikap